2004
DOI: 10.1093/jurban/jth091
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Overweight in Five- to Six-Year-Old Hispanic-American Children: A Pilot Study

Abstract: The objective of this study was to determine the prevalence of and possible risk factors for overweight in a sample of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 37 publications
12
138
1
2
Order By: Relevance
“…In addition, consistent with as expected, this study also found lower BMI scores among children of bilingual Hispanic mothers compared with those of home-language Hispanic mothers. However, as found in prior research (Ariza et al 2004;Sussner et al 2008), maternal acculturation was not associated with probabilities of being overweight and obese among children of Hispanic mothers. Nevertheless, it is notable that lower BMI scores were found among children of bilingual Hispanic mothers, a group who may be acculturating and at the same time maintaining their traditional protective factors for children's health (e.g., traditional foods and dietary practices).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In addition, consistent with as expected, this study also found lower BMI scores among children of bilingual Hispanic mothers compared with those of home-language Hispanic mothers. However, as found in prior research (Ariza et al 2004;Sussner et al 2008), maternal acculturation was not associated with probabilities of being overweight and obese among children of Hispanic mothers. Nevertheless, it is notable that lower BMI scores were found among children of bilingual Hispanic mothers, a group who may be acculturating and at the same time maintaining their traditional protective factors for children's health (e.g., traditional foods and dietary practices).…”
Section: Discussionsupporting
confidence: 64%
“…However, the significant influence vanished at age 36 months, and other acculturation measures were not associated with children's BMI at both 24 and 36 months. In another study, using a sample of two hundred fifty 5-to 6-year-old children of predominantly Mexican immigrant families living in Chicago, Ariza et al (2004) found that there was no significant association between child overweight status and maternal acculturation measured using a scale describing language, social relations, and media use. Using data from the ECLS-B, another study reported no association between maternal acculturation (i.e., language use at home, nativity, and years residing in the USA) and Latino children's BMI at 24 months of age (Fuller et al 2009).…”
Section: Prior Research On Parental Acculturation and Child Weight Dementioning
confidence: 97%
See 1 more Smart Citation
“…A similar trend among boys has been seen in the past decade in Portugal, Spain, Greece and Denmark, which researchers attributed to boys spending a large amount of free time on video games (30,(50)(51)(52) . Studies also show that watching TV encourages more frequent consumption of high-energy snacks (27,28,49,53,54) , which is undoubtedly influenced by TV commercials. It is estimated that almost 50 % of TV advertising directed to children relates to food products, where 91 % are high in sugar, fat and salt (27,29,51) .…”
Section: Discussionmentioning
confidence: 99%
“…Na Cidade de Chihuahua, o autor verificou que as respectivas prevalências, segundo o sexo, apresentaram valores similares aos encontrados em El Paso. Ariza et al 23 , em estudo transversal conduzido com 250 crianças americanas de origem mexicana, em idade pré-escolar (5-6 anos) e residentes em áreas urbanas de Chicago, em 1996, detectaram prevalência de sobrepeso da ordem de 23%. Entre os fatores de risco incluí-dos no estudo, os autores identificaram que assistir à TV por mais que 3 horas/semana (OR = 3,7; IC95%: 1,2-11,0) e consumir diariamente refrigerantes (OR = 5,9; IC95%: 1,2-29) foram considerados importantes preditores para o sobrepeso.…”
Section: Discussionunclassified